2004
DOI: 10.5014/ajot.58.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality of Life for Persons With Alzheimer’s Disease and Their Family Caregivers: Brief Occupational Therapy Intervention

Abstract: Individualized occupational therapy intervention based on the person-environment fit model appears effective for both caregivers and clients. This is especially important in light of a recent directive for more favorable reimbursement for occupational therapy services for persons with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 37 publications
0
79
0
3
Order By: Relevance
“…Their spouses are in similar circumstances (Ulstein, 2009). Family members' lives are closely entangled (Dooley & Hinojosa, 2004), which means that the entire family is more severely afflicted than those of older families (Svanberg, Spector, & Scott, 2011). The dialogue with family members enabled us to grasp fluctuating everyday realities, as they talked about their actions and relations, and reactions activated throughout a day.…”
Section: Research Design and Ethical Considerationsmentioning
confidence: 99%
“…Their spouses are in similar circumstances (Ulstein, 2009). Family members' lives are closely entangled (Dooley & Hinojosa, 2004), which means that the entire family is more severely afflicted than those of older families (Svanberg, Spector, & Scott, 2011). The dialogue with family members enabled us to grasp fluctuating everyday realities, as they talked about their actions and relations, and reactions activated throughout a day.…”
Section: Research Design and Ethical Considerationsmentioning
confidence: 99%
“…According to the recent research, occupational therapy interventions in people with Alzheimer's are effective in the improvement of their quality of life as well as an increase in their participation (13)(14)(15)(16). There are several assessment scales that could be used to assess Alzheimer's patients (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Medically, dementia of the Running head: DEMENTIA CONTEXT 4 progressive type is defined as a chronic, progressive disease with an irreversible deterioration of cognition that typically advances over 8-10 years (Alzheimer's Society, 2013; Merck Manual for Health Care Professionals, 2013). As numerous scholars have observed, most of the medical literature portrays the disability associated with dementia as a personal tragedy (Swain et al, 2003;Volicer, 2005) for both persons with dementia and their families (Dooley & Hinojosa, 2004;Gitlin, et al, 2003;Miyamoto, Tachimori, & Ito, 2010). Further, the depictions that appear in the media typically cast this disease as destructive, mysterious, frightening, unforgiving, crippling, and ultimately fatal (Goldberg, 1996;Hyman, 2008;Media Smarts, n.d., National Institute on Aging, 2012).…”
Section: Dementia In the Context Of Disabilitymentioning
confidence: 99%
“…Most caregivers are unpaid, informal caregivers who tend to be family members. Although caring can be a positive experience, the majority of information on the culture of dementia caregivers pertain to burden and stress (Dooley & Hinojosa, 2004;Gitlin et al, 2003;Miyamoto, Tachimori, & Ito, 2010;Volicer, 2005). As Sarah's dementia continues to progress, Mary reported that Sarah will likely move back in with her.…”
Section: Caregiver Burdenmentioning
confidence: 99%